2002
DOI: 10.2134/agronj2002.8150
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nitrogen Use Efficiency in Cereal Grain Production with Optical Sensing and Variable Rate Application

Abstract: ABSTRACTand Ͼ10% in corn (Hilton et al., 1994). Fertilizer N losses due to surface runoff range between 1 and 13%In 2001, N fertilizer prices nearly doubled as a result of increased (Blevins et al., 1996; Chichester and Richardson, 1992 23% of the total N applied (Drury et al., 1996). In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
225
1
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 520 publications
(252 citation statements)
references
References 26 publications
12
225
1
14
Order By: Relevance
“…Active-light sensor measurements have also been shown to be associated with CM readings (Fig. 3), and have been successfully used in determining variable-rate N applications in wheat (Raun et al, 2002). Sensor reflectance measurements of winter wheat converted to NDVI were used to calculate a response index (determined by comparing to a non-N limiting reference strip) and showed that early-season sensing and treatment of each 1 m 2 resulted in NUE increases of 15% over that of current whole-field techniques based on mass-balance approaches.…”
Section: Ground-based Remote Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Active-light sensor measurements have also been shown to be associated with CM readings (Fig. 3), and have been successfully used in determining variable-rate N applications in wheat (Raun et al, 2002). Sensor reflectance measurements of winter wheat converted to NDVI were used to calculate a response index (determined by comparing to a non-N limiting reference strip) and showed that early-season sensing and treatment of each 1 m 2 resulted in NUE increases of 15% over that of current whole-field techniques based on mass-balance approaches.…”
Section: Ground-based Remote Sensingmentioning
confidence: 99%
“…The methodology developed for wheat by Raun et al (2002) relies on the ability to estimate crop N demand from early season growth. This is done by dividing the sensed NDVI by the days from planting to the day of sensing (http://www.nue.okstate.edu), which is essentially the earlyseason growth rate or biomass production per day.…”
Section: Ground-based Remote Sensingmentioning
confidence: 99%
“…Active crop canopy reflectance sensors have been studied as a ground-based sensing tool to assess in-season plant nitrogen (N) status and to direct spatially-variable N applications (Dellinger et al 2008;Raun et al 2002;Raun et al 2005;Roberts et al 2009;Schmidt et al 2009;Shanahan et al 2008;Solari et al 2008). Active sensors are commercially available tools that generate modulated light in the visible (VIS; 400-700 nm) and near-infrared (NIR; 700-1000 nm) regions of the electromagnetic spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…A maioria das metodologias propostas na literatura para direcionar a aplicação de N por meio de sensores de dossel levam em conta a estimativa de produtividade de forma espacializada realizada por esse equipamento (GIRMA et al, 2006;GROHS et al, 2009;KITCHEN et al, 2010;LUKINA et al, 2001;RAUN et al, 2005RAUN et al, , 2002SOLIE et al, 2012;TEAL et al, 2006 Figura 2.4 -Coeficiente de determinação (R 2 ), inclinação da reta, raiz quadrada do erro médio (RMSE) e equivalente de sensibilidade (SEq=inclinação/RMSE) das relações entre os índices de vegetação/bandas espectrais e a produtividade de colmos da cana-de-açúcar nas duas áreas e seis variedades analisadas em conjunto por meio da normalização dos dados Apesar da maior sensibilidade do MTCI, a relação desse IV com a produtividade foi semelhante à do reNDVI, mas apresentando menor dispersão dos dados, o que resultou em uma redução no erro da estimativa de apenas 6,7% (0,59 t ha -1 ) (Figuras 2.5 e 2.6).…”
Section: Relação Entre íNdices De Vegetação E Produtividade Da Cana-dunclassified
“…Diversos estudos vêm sendo conduzidos em culturas altamente domesticadas, como é o caso do milho (HOLLAND; SCHEPERS, 2010;KITCHEN et al, 2010;SOLARI et al, 2008;SOLIE et al, 2012;TEAL et al, 2006) e do trigo (BERNTSEN et al, 2006;GROHS et al, 2009;LUKINA et al, 2001;RAUN et al, 2002;SOLIE et al, 2012;WRIGHT et al, 2004). Ambos os casos mostram resultados promissores de aumento da eficiência do uso de N, redução da aplicação de fertilizantes e/ou aumento da produtividade.…”
Section: Introductionunclassified